Inhibition of human macrophage activation via pregnane neurosteroid interactions with toll-like receptors: Sex differences and structural requirements - Balan, Irina; Aurelian, Laure; Williams, Kimberly S.; Campbell, Brian; Meeker, Rick B.; Morrow, A. Leslie (Frontiers in Immunology, 2022)
We recently discovered that (3α,5α)3-hydroxypregnan-20-one (allopregnanolone) inhibits pro-inflammatory toll-like receptor (TLR) activation and cytokine/chemokine production in mouse macrophage RAW264.7 cells. The present studies evaluate neurosteroid actions upon TLR activation in human macrophages from male and female healthy donors. Buffy coat leukocytes were obtained from donors at the New York Blood Center (http://nybloodcenter.org/), and peripheral blood mononuclear cells were isolated/cultured to achieve macrophage differentiation. TLR4 and TLR7 were activated by lipopolysaccharide (LPS) or imiquimod in the presence/absence of allopregnanolone or related neurosteroids and pro-inflammatory markers were detected by ELISA or western blotting. Cultured human monocyte-derived-macrophages exhibited typical morphology, a mixed immune profile of both inflammatory and anti-inflammatory markers, with no sex difference at baseline. Allopregnanolone inhibited TLR4 activation in male and female donors, preventing LPS-induced elevations of TNF-, MCP-1, pCREB and pSTAT1. In contrast, 3α,5α-THDOC and SGE-516 inhibited the TLR4 pathway activation in female, but not male donors. Allopregnanolone completely inhibited TLR7 activation by imiquimod, blocking IL1-β, IL6, pSTAT1 and pIRF7 elevations in females only. 3α,5α-THDOC and SGE-516 partially inhibited TLR7 activation, only in female donors. The results indicate that allopregnanolone inhibits TLR4 and TLR7 activation in cultured human macrophages resulting in diminished cytokine/chemokine production. Allopregnanolone inhibition of TLR4 activation was found in males and females, but inhibition of TLR7 signals exhibited specificity for female donors. 3α,5α-THDOC and SGE-516 inhibited TLR4 and TLR7 pathways only in females. These studies demonstrate anti-inflammatory effects of allopregnanolone in human macrophages for the first time and suggest that inhibition of pro-inflammatory cytokines/chemokines may contribute to its therapeutic actions.